Infant-Family Mental Health in the NICU: A Mixed-Methods Study Exploring Referral Pathways and Family Engagement. Issue 1 (January 2021) - Driver, Myisha; Mikhail, Sandra; Carson, Melissa C.; Lakatos, Patricia P.; Matic, Tamara; Chin, Steven; Williams, Marian E.
Abstract : Parents and infants in the neonatal intensive care unit (NICU) are exposed to considerable stress, and infant-family mental health (IFMH) services foster emotional well-being in the context of the parent-infant relationship. This mixed-methods study examined the role of an IFMH program introduced in a level 4 NICU. The study included (1) retrospective medical record review of NICU patients who were referred to the IFMH program and (2) qualitative interviews with NICU nurse managers, neonatologists, and medical social workers to explore their understanding of the IFMH program, explore the referral pathways and factors that supported family engagement, and identify specific recommendations for program improvement. Of the 311 infant-parent dyads referred to the IFMH program, 62% had at least one session and Spanish-speaking families were more likely to engage. Of those families receiving services, about one-third had brief intervention, one-third had 4 to 10 sessions, and one-third had long-term services, including in-home after-discharge services. Qualitative interviews with health providers identified unique qualities of the IFMH program and why families were and were not referred to the program. Recommendations centered on adding a full-time IFMH mental health provider to the NICU and increasing communication and integration between the IFMH program and the medical team.